CHI '13 Extended Abstracts on Human Factors in Computing Systems 2013
DOI: 10.1145/2468356.2468616
|View full text |Cite
|
Sign up to set email alerts
|

Improving user comfort and office energy efficiency with POEM (personal office energy monitor)

Abstract: Consensus exists in much of industry and academia that engaging end-users is an essential element for improving energy efficiency in office buildings.We present our experiences implementing and deploying POEM (Personal Office Energy Monitor) with real office users. POEM is an end-user eco-feedback application. It provides detailed personalized data on energy usage and ambient conditions to each office user, as well as reporting aggregates for building-level management and policy setting. The POEM UI also allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Milenkovic et al have demonstrated that, as a result, staff typically feel low levels of control over their personal comfort [27]. Smart heating systems have been explored in recent ubicomp research.…”
Section: Related Workmentioning
confidence: 99%
“…Milenkovic et al have demonstrated that, as a result, staff typically feel low levels of control over their personal comfort [27]. Smart heating systems have been explored in recent ubicomp research.…”
Section: Related Workmentioning
confidence: 99%
“…Heating accounts for a significant proportion of workplace energy costs -between 20-40% in office-based organizations [5] -and is linked to the comfort of staff. Milenkovic et al have demonstrated that -using traditional heating controls -staff typically feel low levels of control over their personal comfort, and have developed POEM -a smart alternative [26]. Other smart solutions have been proposed [19,12], and research suggests that pursuing personal comfort may reduce collective energy consumption [7], but such proposals are complicated to implement and as yet have little hard evidence to demonstrate impact.…”
Section: Related Workmentioning
confidence: 99%
“…For example, smiley faces that get grumpy the more power used, power gauges that move from green zones to red zones of the dial if the power use goes above the average, and graphical comparisons of current use against local use or personal pre-set goals. POEM (Personal Office Energy Monitor) (Milenkovic et al, 2013) is a general application that runs on desktop computers. It provides personalized data on electricity usage for a workplace.…”
Section: Related Workmentioning
confidence: 99%
“…For example, a pragmatic visualization of electricity consumption could be a graph that displays kilowatt-hours used over time (e.g. Froehlich et al, 2012;Kjeldskov et al, 2012;Milenkovic et al, 2013;Schwarz et al, 2013). Alternatively, Kim et al (2009) use an artistic representation of power consumption in their system, Coralog, which displays a coral reef that changes colour and condition according to electricity usage.…”
Section: Related Workmentioning
confidence: 99%